Structural Analysis of Folded Glass Plate Structures - J. Griffith (Challenging Glass Conference, 2016)
Folded glass plate structures have the potential to become the next generation of structural glass. By connecting glass plates along their edges and creating a folded plate geometry, glass can be used to transparently self-span large areas without the need for additional supporting structure. An experimental glass connection is used as a basis for this paper. Available test and numerical data is used to create an interaction diagram for this connection, giving allowable axial forces, shear forces and bending moments. Due to the dependency of folded plate structures on geometry, a parametric numerical analysis approach is developed. This captures the global behaviour of the structures whilst also being calibrated against the local behaviour of the connection detail. The approach is based on established techniques for structural glass analysis using the finite element software Strand7. The results are presented graphically, illustrating that connection utilization drives design. It is shown that parametric finite element analysis is a powerful tool to extend feasibility-studies for new shapes and configurations.